Altered Balance of Activity in the Striatal Direct and Indirect Pathways in Mouse Models of Huntington's Disease - Andre, Veronique M.; Fisher, Yvette E.; Levine, Michael S. (Frontiers in Systems Neuroscience, 2011)
Imbalance in the activity of striatal direct and indirect pathway neurons contributes to motor disturbances in several neurodegenerative diseases. In Huntington's disease (HD), indirect pathway [dopamine (DA) D2 receptor-expressing] medium-sized spiny neurons (MSNs) are believed to show earlier vulnerability than direct pathway MSNs. We examined synaptic activity and DA modulation in MSNs forming the direct and indirect pathways in YAC128 and BACHD mouse models of HD. To visualize the two types of MSNs, we used mice expressing enhanced green fluorescent protein under the control of the promoter for the DA D1 or D2 receptor. Experiments were performed in early symptomatic (1.5 months) and symptomatic (12 months) mice. Behaviorally, early symptomatic mice showed increased stereotypies while symptomatic mice showed decreased motor activity. Electrophysiologically, at the early stage, excitatory and inhibitory transmission onto D1-YAC128 and D1-BACHD MSNs were increased, while there was no change in D2 MSNs. DA modulation of spontaneous excitatory postsynaptic currents (sEPSCs) in slices was absent in YAC128 cells at the early stage, but was restored by treating the slices with the DA depleter tetrabenazine (TBZ). In BACHD mice TBZ restored paired-pulse ratios and a D1 receptor antagonist induced a larger decrease of sEPSCs than in D1-WT cells, suggesting increased DA tone. Finally, TBZ decreased stereotypies in BACHD mice. These results indicate that by reducing DA or antagonizing D1 receptors, increases in inhibitory and excitatory transmission in early phenotypic direct pathway neurons can be normalized. In symptomatic YAC128 mice, excitatory synaptic transmission onto D1 MSNs was decreased, while inhibitory transmission was increased in D2 MSNs. These studies provide evidence for differential and complex imbalances in glutamate and GABA transmission, as well as in DA modulation, in direct and indirect pathway MSNs during HD progression.